Role of Strategic Leadership in Achieving University Governance Requirements: A Survey of a Sample of Teaching Staff at College of Administration and Economics/University of Mosul - Al-Taha, Shihab Mohammed (Journal of Economics and Administrative Sciences, 2021)
Aim of the Study: The paper aims at identifying the extent of the role of strategic leadership represented by its four dimensions (administrative, transformational, political, moral) in fulfilling the requirements of university governance (Context, message and Goal, Management orientation, Independence, Issue, Sharing) Methodology: A survey is applied to (107) members of the teaching staff at the college of Administration and Economics/ University of Mosul. To achieve the goals of the study, the researcher makes use of a number of tools such as: questionnaire, statistical tools and methods (repetitions, percentage, arithmetic mean, standard deviation, response rate, difference coefficient, correlation coefficient, linear regression) via using (SPSS). Limits of the Study: The paper demonstrates on providing the requirements of preparing an applied framework. Scientific contribution: In order to fulfill aims of the study and depending on the results, it has bee found that there is a positive moral relationship between the two variables as well as a statistically significant effect of the dimensions of the strategic leadership fulfilling to the requirements of university governance. It is also found that the moral dimension of strategic leadership has greater influence in university governance if compared to the transformative dimension. Social Contribution: The researcher presents a set of recommendations, and the most prominent one is the necessity of focusing on the moral dimension of strategic leadership due to its most influential role in achieving the requirements of university governance. Also, the study recommends paying attention to the transformative dimension in order to strengthen level of its impact on university governance. Value of the Study: The value of the study lies in its focusing on the importance of current paper variables in managerial specialties